Severe Asthma Phenotypes: Challenges and Options for Control (Actualité en allergologie et en immunologie au Canada, 2023)
The practice of medicine has evolved from “arm-chair medicine” through “evidence-based medicine” to “precision medicine”. Medical literature has seen a proliferation of the use of the phrases “precision medicine” and “personalized medicine,” with little distinction made between the two. While both strategies promote individualizing patient care, precision medicine is guided by information based on the genes, proteins, metabolites, and other biomarkers in the human body. In addition to these biological markers, personalized medicine would consider various social, economic, behavioural, and environmental factors that might be specific to a particular individual in planning a treatment strategy unique to that individual. The term P4 Medicine (Predictive, Preventive, Personalized and Participatory) has also been proposed to reflect the increased understanding and implications of the pathobiology of disease on management strategies.1 The use of biologics and cell-based therapies, particularly in cancer therapeutics, has demonstrated the power of these strategies.2 This brief review will focus on how this strategy is currently being applied in the management of severe asthma.